Ganglioneuroblastoma of the thoracic spinal cord: a very rare case report. - Akgun, Bekir; Ates, Deniz; Kaplan, Metin (My University, 2012)
An eight-month-old male child was admitted with weakness and swelling in the feet. Paraparesis and bilateral lower extremity edema were present in the neurological examination. Thoracic MRI showed an intradural intramedullary mass 61 x 11 mm in size in the T5-T10 levels. Laminotomy between the T5-T10 vertebrae was performed. A mass with smooth borders was separated from most of the neural tissue. In the postoperative MRI, we observed a contrast enhancing area, considered a residual fragment, only 5 x 4 mm in size. Histopathological properties were compatible with the intermixed subtype of ganglioneuroblastoma. Only a limited number of thoracic cord Ganglioneuroblastoma reports have been previously published. Although very rare in children and young adults, ganglioneuroblastoma should be included in the differential diagnosis of thoracic cord tumors. It is difficult to obtain a preoperative diagnosis with clinical features and radiological investigations. Diagnosis depends on histopathological examinations. Curative treatment should be in the form of a complete resection of the tumor. In partially resected cases, adjuvant radiotherapy may become necessary, along with close follow-up.
Keywords: Ganglioneuroblastoma; Humans; Infant; Magnetic Resonance Imaging; Male; Spinal Cord Neoplasms; Thoracic Vertebrae; article; case report; human; infant; male; neuroblastoma; nuclear magnetic resonance imaging; spinal cord tumor; vertebra